Algebra Questions

Question Number 105448 by bemath last updated on 29/Jul/20

$$\mathcal{G}{iven}\:\begin{cases}{\frac{\mathrm{4}{x}^{\mathrm{2}} }{\mathrm{4}{x}^{\mathrm{2}} +\mathrm{1}}\:=\:{y}}\\{\frac{\mathrm{4}{y}^{\mathrm{2}} }{\mathrm{4}{y}^{\mathrm{2}} +\mathrm{1}}\:=\:{z}}\\{\frac{\mathrm{4}{z}^{\mathrm{2}} }{\mathrm{4}{z}^{\mathrm{2}} +\mathrm{1}}\:=\:{x}}\end{cases}\:\:\:.\:{find} \\$$$${x}+{y}+{z}\:?\: \\$$

Commented by john santu last updated on 29/Jul/20

$$\:\frac{\mathrm{1}}{{x}}+\frac{\mathrm{1}}{{y}}+\frac{\mathrm{1}}{{z}}=\:\frac{\mathrm{4}{x}^{\mathrm{2}} +\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} }+\frac{\mathrm{4}{y}^{\mathrm{2}} +\mathrm{1}}{\mathrm{4}{y}^{\mathrm{2}} }+\frac{\mathrm{4}{z}^{\mathrm{2}} +\mathrm{1}}{\mathrm{4}{z}^{\mathrm{2}} } \\$$$$\frac{\mathrm{1}}{{x}}+\frac{\mathrm{1}}{{y}}+\frac{\mathrm{1}}{{z}}=\:\mathrm{3}+\frac{\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} }+\frac{\mathrm{1}}{\mathrm{4}{y}^{\mathrm{2}} }+\frac{\mathrm{1}}{\mathrm{4}{z}^{\mathrm{2}} } \\$$$$\frac{\mathrm{1}}{{x}}+\frac{\mathrm{1}}{{y}}+\frac{\mathrm{1}}{{z}}=\mathrm{3}+\left(\frac{\mathrm{1}}{\mathrm{2}{x}}\right)^{\mathrm{2}} +\left(\frac{\mathrm{1}}{\mathrm{2}{y}}\right)^{\mathrm{2}} +\left(\frac{\mathrm{1}}{\mathrm{2}{z}}\right)^{\mathrm{2}} \\$$$$\frac{\mathrm{1}}{{x}}+\frac{\mathrm{1}}{{y}}+\frac{\mathrm{1}}{{z}}=\mathrm{3}+\frac{\mathrm{1}}{\mathrm{4}}\left\{\left(\frac{\mathrm{1}}{{x}}\right)^{\mathrm{2}} +\left(\frac{\mathrm{1}}{{y}}\right)^{\mathrm{2}} +\left(\frac{\mathrm{1}}{{z}}\right)^{\mathrm{2}} \right\} \\$$$$\begin{cases}{{set}\:\frac{\mathrm{1}}{{x}}={a},\:\frac{\mathrm{1}}{{y}}={b},\:\frac{\mathrm{1}}{{z}}={c}\:\left.\begin{matrix}{}\\{}\end{matrix}\right\}}\end{cases} \\$$$$\Leftrightarrow\:{a}+{b}+{c}\:=\:\mathrm{3}\:+\frac{\mathrm{1}}{\mathrm{4}}\left\{\left({a}+{b}+{c}\right)^{\mathrm{2}} −\mathrm{2}\left({ab}+{ac}+{bc}\right)\right\} \\$$$$\\$$

Commented by behi83417@gmail.com last updated on 29/Jul/20

$$\mathrm{x}=\mathrm{y}=\mathrm{z}=\mathrm{0}\:\mathrm{and}:\mathrm{4x}^{\mathrm{2}} −\mathrm{4x}+\mathrm{1}=\mathrm{0}\Rightarrow\mathrm{x}=\mathrm{y}=\mathrm{z}=\frac{\mathrm{1}}{\mathrm{2}} \\$$$$\mathrm{if}:\mathrm{x}\neq\mathrm{y}\neq\mathrm{z}\neq\mathrm{0}\Rightarrow\mathrm{x}=\frac{\mathrm{1}}{\mathrm{2a}},\mathrm{y}=\frac{\mathrm{1}}{\mathrm{2b}},\mathrm{z}=\frac{\mathrm{1}}{\mathrm{2c}}\Rightarrow \\$$$$\begin{cases}{\frac{\mathrm{4}.\frac{\mathrm{1}}{\mathrm{4a}^{\mathrm{2}} }}{\mathrm{4}.\frac{\mathrm{1}}{\mathrm{4a}^{\mathrm{2}} }+\mathrm{1}}=\frac{\mathrm{1}}{\mathrm{2b}}\Rightarrow\begin{cases}{\frac{\mathrm{1}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }=\frac{\mathrm{1}}{\mathrm{2b}}}\\{\frac{\mathrm{1}}{\mathrm{1}+\mathrm{b}^{\mathrm{2}} }=\frac{\mathrm{1}}{\mathrm{2c}}\Rightarrow}\end{cases}}\\{}\end{cases} \\$$$$\Rightarrow\begin{cases}{\mathrm{a}^{\mathrm{2}} +\mathrm{1}=\mathrm{2b}}\\{\mathrm{b}^{\mathrm{2}} +\mathrm{1}=\mathrm{2c}}\\{\mathrm{c}^{\mathrm{2}} +\mathrm{1}=\mathrm{2a}}\end{cases}\Rightarrow\left(\mathrm{a}−\mathrm{1}\right)^{\mathrm{2}} +\left(\mathrm{b}−\mathrm{1}\right)^{\mathrm{2}} +\left(\mathrm{c}−\mathrm{1}\right)^{\mathrm{2}} =\mathrm{0} \\$$$$\Rightarrow\mathrm{a}=\mathrm{b}=\mathrm{c}=\mathrm{1}\Rightarrow\mathrm{x}=\mathrm{y}=\mathrm{z}=\frac{\mathrm{1}}{\mathrm{2}} \\$$

Answered by ajfour last updated on 29/Jul/20

$${let}\:\:\:\frac{\mathrm{1}}{{x}}={p}\:\:\:,\:\:\frac{\mathrm{1}}{{y}}={q}\:\:,\:\:\frac{\mathrm{1}}{{z}}={r} \\$$$$\Rightarrow\:\:\frac{\mathrm{4}}{\mathrm{4}−{p}^{\mathrm{2}} }=\frac{\mathrm{1}}{{q}}\:,\:\:\:\frac{\mathrm{4}}{\mathrm{4}\left(\frac{{q}}{{p}}\right)^{\mathrm{2}} +{q}^{\mathrm{2}} }=\:\frac{\mathrm{1}}{{r}}\:, \\$$$$\:\:\:\:\:\:\frac{\mathrm{4}}{\mathrm{4}+{r}^{\mathrm{2}} }=\frac{\mathrm{1}}{{p}} \\$$$$\Rightarrow\:\:\mathrm{4}−{p}^{\mathrm{2}} =\mathrm{4}{q}\:\:\:\:...\left({i}\right) \\$$$$\:\mathrm{4}\left(\frac{{q}}{{p}}\right)^{\mathrm{2}} +{q}^{\mathrm{2}} =\mathrm{4}{r}\:\:\Rightarrow\:\:{q}^{\mathrm{2}} \left(\frac{\mathrm{1}}{{p}^{\mathrm{2}} }+\frac{\mathrm{1}}{\mathrm{4}}\right)={r}\:\:\:..\left({ii}\right) \\$$$$\:\:\:\:\:\:\:\mathrm{4}+{r}^{\mathrm{2}} =\mathrm{4}{p}\:\:\:\:\:\:\:...\left({iii}\right) \\$$$$\Rightarrow\:\:\:\left(\mathrm{1}−\frac{{p}^{\mathrm{2}} }{\mathrm{4}}\right)^{\mathrm{2}} \left(\frac{\mathrm{1}}{{p}^{\mathrm{2}} }+\frac{\mathrm{1}}{\mathrm{4}}\right)^{\mathrm{2}} =\mathrm{4}\left({p}−\mathrm{1}\right) \\$$$$\Rightarrow\:\:\:\:\left(\mathrm{16}−{p}^{\mathrm{4}} \right)^{\mathrm{2}} =\mathrm{64}×\mathrm{16}{p}^{\mathrm{4}} \left({p}−\mathrm{1}\right) \\$$$$......{degree}\:\mathrm{8} \\$$

Answered by bramlex last updated on 29/Jul/20

$$\frac{\mathrm{1}}{{y}}\:=\:\frac{\mathrm{4}{x}^{\mathrm{2}} +\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} }\:\rightarrow\frac{\mathrm{1}}{{y}}\:=\:\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} } \\$$$$\rightarrow\frac{\mathrm{1}}{{z}}\:=\:\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} }\right)^{\mathrm{2}} \\$$$$\rightarrow\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}{z}^{\mathrm{2}} }\:=\:\frac{\mathrm{1}}{{x}} \\$$$$\rightarrow\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\left\{\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}{x}^{\mathrm{2}} }\right)^{\mathrm{2}} \right\}=\:\frac{\mathrm{1}}{{x}} \\$$$${set}\:\frac{\mathrm{1}}{{x}}\:=\:{m}\: \\$$$$\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\left\{\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}{m}^{\mathrm{2}} \right)^{\mathrm{2}} \right\}\:=\:{m}\: \\$$$$\frac{\mathrm{5}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{4}}\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2}}{m}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{16}}{m}^{\mathrm{4}} \right)={m} \\$$$$\mathrm{20}+\mathrm{4}+\mathrm{2}{m}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{4}}{m}^{\mathrm{4}} =\mathrm{16}{m} \\$$$${m}^{\mathrm{4}} +\mathrm{32}{m}^{\mathrm{2}} −\mathrm{256}{m}+\mathrm{16}×\mathrm{24}=\mathrm{0} \\$$

Answered by 1549442205PVT last updated on 07/Aug/20

$$\mathrm{WLOG}\:\mathrm{suppose}\:\mathrm{that}\:\mathrm{x}\geqslant\mathrm{y}\geqslant\mathrm{z}\geqslant\mathrm{0}\:\left(\mathrm{1}\right).\mathrm{Then} \\$$$$\frac{\mathrm{4z}^{\mathrm{2}} }{\mathrm{4z}^{\mathrm{2}} +\mathrm{1}}\geqslant\frac{\mathrm{4x}^{\mathrm{2}} }{\mathrm{4x}^{\mathrm{2}} +\mathrm{1}}\geqslant\frac{\mathrm{4y}^{\mathrm{2}} }{\mathrm{4y}^{\mathrm{2}} +\mathrm{1}}\geqslant\mathrm{0} \\$$$$\Rightarrow\frac{\mathrm{z}^{\mathrm{2}} }{\mathrm{4z}^{\mathrm{2}} +\mathrm{1}}\geqslant\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{4x}^{\mathrm{2}} +\mathrm{1}}\Rightarrow\mathrm{z}^{\mathrm{2}} \left(\mathrm{4x}^{\mathrm{2}} +\mathrm{1}\right)\geqslant\mathrm{x}^{\mathrm{2}} \left(\mathrm{4z}^{\mathrm{2}} +\mathrm{1}\right) \\$$$$\Rightarrow\mathrm{z}^{\mathrm{2}} \geqslant\mathrm{x}^{\mathrm{2}} \Rightarrow\mathrm{z}\geqslant\mathrm{x}\geqslant\mathrm{0}\left(\mathrm{2}\right).\mathrm{From}\:\left(\mathrm{1}\right)\:\mathrm{and}\left(\mathrm{2}\right) \\$$$$\mathrm{we}\:\mathrm{get}\:\mathrm{x}=\mathrm{y}=\mathrm{z}.\mathrm{Hence} \\$$$$\frac{\mathrm{4x}^{\mathrm{2}} }{\mathrm{4x}^{\mathrm{2}} +\mathrm{1}}=\mathrm{x}\Leftrightarrow\mathrm{4x}^{\mathrm{3}} −\mathrm{4x}^{\mathrm{2}} +\mathrm{x}=\mathrm{0} \\$$$$\Leftrightarrow\mathrm{x}\left(\mathrm{4x}^{\mathrm{2}} −\mathrm{4x}+\mathrm{1}\right)=\mathrm{0}.\Leftrightarrow\mathrm{x}\left(\mathrm{2x}−\mathrm{1}\right)^{\mathrm{2}} =\mathrm{0} \\$$$$\Leftrightarrow\boldsymbol{\mathrm{x}}\in\left\{\mathrm{0};\frac{\mathrm{1}}{\mathrm{2}}\right\} \\$$$$\mathrm{Thus},\mathrm{the}\:\mathrm{roots}\:\mathrm{of}\:\mathrm{the}\:\mathrm{given}\:\mathrm{system}\:\mathrm{are}: \\$$$$\left\{\left(\mathrm{0};\mathrm{0}\right);\left(\frac{\mathrm{1}}{\mathrm{2}};\frac{\mathrm{1}}{\mathrm{2}}\right)\right\} \\$$

Commented by behi83417@gmail.com last updated on 31/Jul/20

$$\mathrm{sir}\:\mathrm{154}!\:\mathrm{there}\:\mathrm{is}\:\mathrm{a}\:\mathrm{typo}\:\mathrm{in}\:\mathrm{line}#\mathrm{5}\:\mathrm{from}\:\mathrm{end}. \\$$

Commented by 1549442205PVT last updated on 01/Aug/20

$$\mathrm{Thank}\:\mathrm{Sir}.\mathrm{I}\:\mathrm{understanded}\:\mathrm{and}\:\mathrm{shall}\: \\$$$$\mathrm{correct}\:\mathrm{it} \\$$